Osnovna obilježja oslovljavanja u Zagrebu - Žic Fuchs, Milena (Array, 1988)
Various forms of address frequently heard in the city of Zagreb are analysed. Data accumulated on the basis of 100 interviews indicate that the official forms of address drug - drugarica (comrade), traditional forms gospodin - gospođa (Mr. - Mrs.) as well as forms belonging to the Zagreb kajkavian dialect (gospon - Mr, gospodična - Miss etc.) in most cases form a complex intermeshed system of address in which certain forms have undergone changes and have acquired specific functions.